Management of Rhegmatogenous Retinal detachment with Buckle Sclera and Cryoretinopexcy - Ria Mutiara; Ramzi Amin (International Journal of Retina, 2018)
Introduction: Retinal detachment is divided into three categories. The most common type is the regmatogen retinal detachment (rhegmatogenous retinal detachment), which is the result of the tearing of the retinal lining. Actions can be Buckle Sclera, vitrectomy pars plana and pneumatic retinopexy. The purpose of this case report to reported Management of Rhegmatogenous Retinal detachment with Buckle Sclera and Cryoretinopexcy. Method: A 58 years old man with chief complaint The left eye blurred like a curtain covered since 5 days,floaters (+), photopsia (+),headache (+), Patients never complain of lost vision suddenly before, eyeball pain is not there.History of trauma (+),On examination, the visual acuity 6/9 RE and 1/60 LE, anterior segment lens cloudy (+)nuclaer gr III, fundus photograph we found retinal contours of the blood vessels well, tear (+) is directed at 2-3 hours of superior-temporal and fovea reflex (-), B-scan ultrasound of the posterior segment the retina is not intact, Membran like lession detachment which attach to optic nerve. Results: The Sclera buckles and cryoretinopexy were performed under general antesthesia. Visual acuity post-operative on left eye 2/60. subconjunctival bleeding (+), the fundus photographs retinal attach but the macular reflex is still negative. post-operative theraphy with topical steroid and antibiotic eye drops, oral antibiotic, and oral analgetic. follow up 1-month post-operative visual acuity 5/60 with fundus photograph obtained retina attach. Conclusion: a diagnosis of retinal detachment can be found, with the discovery of fullthickness breaks or defects occurring from the retinal neurosensory, this break will allow the vitreous to enter the defect gap between the retinal neurosensory and RPE. Based on the clinical features of the posterior segment, the detachment area was found with the location of the Linchoff Rule 2 break based on the American Academy of Ophthalmology. The objective of operative therapy was to reattach the retinal portion of which one of them was buckle sclera and cryoretinopexcy.